Inflammatory Vegetative Lesions of the Perineum: A Rare and Severe Clinical Presentation of Netherton Syndrome - Shatha Albluwi; Aude Maza; Maella Severino-Freire; Emilie Tournier; Juliette Mazereeuw-Hautier (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)